Knowledge Level Relationship With Community Behavior Concerning Mask Use During The Covid-19 Pandemic In Langkat District, North Sumatera Province - Dwi Rohyani; Ananda, Dwi (STIKES Nani Hasanuddin Makassar, 2021)
Covid-19 is a disease caused by coronavirus. One of the steps that can limit the spread of the Covid-19 virus is wearing a mask. However, there are still some people who do not use masks. The reason is uncomfortable, going to a place that is close to the house, and difficulty breathing. The behavior of people who do not use masks is due to public ignorance of the importance of using masks. This study aims to analyze the relationship between the level of knowledge and people's behavior regarding the use of masks during the Covid-19 pandemic in the VIII Environment of Dendang Village, Stabat District, Langkat Regency, North Sumatra Province. This study is correlational with a cross sectional approach. The sample in this study was 135 people. The results showed that the level of public knowledge about masks was still not which was 76 respondents (56.3%) and the majority of people who behaved badly which was 74 respondents (54.8%). This means that there is a relationship between the level of knowledge and the behavior of respondents regarding the use of masks during the Covid-19 pandemic with a value of p = 0.000 (<0.05). People must take care of their own health by always using the correct and appropriate mask as determined by the Government as a form of self-protection from the Covid-19 virus.